Phenotypical changes and clinical significance of CD4+/CD8+ T cells in SLE - Yuan, Shiwen; Zeng, Yanting; Li, Jiawei; Wang, Cuicui; Li, Weinian; He, Zhixiang; Ye, Jinghua; Li, Fangfei; Chen, Yi; Lin, Xiaojun; Yu, Na; Cai, Xiaoyan (Lupus science & medicine, 2022)
ObjectiveT cells display significant phenotypical changes and play multiple roles in promoting the immune response in SLE. The frequencies of T cell subpopulations in SLE are still not well understood. To better understanding the phenotypic abnormalities of T cells in SLE will help us to clarify disease immunopathology and to find promising biomarkers for disease monitoring and control.MethodsPeripheral blood CD4+ and CD8+ T cells and their subsets were determined by flow cytometry. Forty-one active SLE patients were selected, including 28 new-onset patients and 13 relapsing patients. One hundred healthy controls (HCs) were enrolled as the control group. The percentages of these cell subsets between patients with SLE and HCs and their relationships with disease activity and autoantibody titers were analysed. Thirteen of 28 new-onset SLE patients were assessed before and after treatment. The changes in the frequencies of these cell subsets and their relationships with renal response were analysed.ResultsThere was a broad range of anomalies in the proportion of T cell subsets in patients with SLE compared with that of the HCs. Compared with the HCs, a higher frequency of memory T cells and a lower frequency of naïve T cells were noted in patients with SLE. In addition, an imbalance of CD28+ and CD28− cells in CD4+ T cells was observed in patients with SLE. We found that the expanded CD4+CD28− T cells did not decrease after treatment in patients who had impaired renal responses. It was very interesting to exhibit a negative correlation in the frequency between the CD4+CD28− T cells and T regulatory (Treg) cells and a positive correlation between the frequency of CD4+CD28+ T cells and Treg cells in this study. Increased CD8+HLADR+ T cell and CD8+CD38+HLADR+ T cell counts were observed in patients with SLE, suggesting an impaired cytotoxic capacity of CD8+ T cells in SLE. Additionally, we found that CD8+CD38+HLADR+ T cells were closely associated with disease activity, autoantibody titres and renal prognosis. CD4+ CXCR5−PD1+ T cells were expanded in patients with SLE in this study and were associated with disease activity in SLE. Th1 (T helper type 1) cells and Treg cells were decreased, but frequencies of T follicular helper (Tfh) cells, Th2 cells, Th17 cells and Tfh17 cells were increased. A strong correlation between Th17 cells and Tregs with renal involvement was observed in this study.ConclusionThe proportions of CD4+CD28− T cells, CD4+CXCR5−PD1+ T cells, CD8+HLADR+ T cells and CD8+CD38+HLADR+ T cells increased in patients with SLE and could be associated with disease activity and renal prognosis.